An Observational Study of Glomerular Functions in Beta-thalassemia Major Children by Schwartz Formula and Technetium 99m Diethylenetriaminepentaacetic Acid Renogram - Sukanta Mandal; Tathagata Bose; Rachna Gulati; Manish Singh Ahuja (Archives of Medicine and Health Sciences)
Background and Aim: Kidney dysfunction is reported in significant number of beta thalassemia major children. The aim of this study was to determine the prevalence of glomerular dysfunction in beta-thalassemia major children on regular blood transfusion (BT) and chelation therapy, and to find the correlation between glomerular filtration rate (GFR) estimated by Schwartz formula and Technetium 99m diethylenetriaminepentaacetic acid (99mTc-DTPA) renogram with ferritin level and cumulative transfusion load. Materials and Methods: An observational cross-sectional study conducted was done on 110 children diagnosed with beta-thalassemia major receiving regular BT and chelation therapy. Clinical examination, biochemical investigations (serum creatinine, ferritin) and DTPA renal scan were done. Estimated GFR calculation was done by Schwartz method and 99mTc-DTPA scan. The normal values of GFR were taken from the standard value as per KDIGO guidelines. P < 0.05 was considered statistically significant. Results: The prevalence of glomerular dysfunction by Schwartz formula and DTPA renogram was 44% and 24%, respectively. The GFR calculation (Schwartz formula and DTPA renogram) were weakly positively correlated (r = 0.126, P = 0.547). There was significant association between GFR Schwartz and duration of iron chelation, as children with abnormal GFR had significantly more duration of iron chelation >5 years (28% vs. 4%, P = 0.003). GFR (Schwartz formula and DTPA renogram) showed no association with cumulative transfusion load and disease duration (P > 0.05). GFR Schwartz formula and GFR–DTPA showed no correlation with serum ferritin with r = 0.179, (P = 0.392) and r = 0.278 (P = 0.178). Conclusion: There is a significant derangement in the renal function of children of beta-thalassemia major on chronic BT and iron chelation therapy. GFR holds a direct correlation with the increasing duration of iron chelation.